Efektivitas Sosialisasi Komisi Pemilihan Umum Daerah pada Pemilih Pemula dalam Pemilu Kepala Daerah di Masa Pandemi Covid 19 - Irsyad Sudirman; Imam Muazansyah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The purpose of the study was to find out the effectiveness of the socialization carried out by the Regional General Election Commission (KPUD) of Bulungan Regency for the beginner voter group in the implementation of the Regional Head Election during the COVID-19 pandemic. The research method uses a qualitative descriptive approach using primary and secondary data types. Methods of collecting data by means of interviews and secondary data documentation. The results showed the effectiveness of the socialization in the form of: Procedures and selection of objectives, utilization of resources, budget, facilities, infrastructure, integration and achievement of objectives, all of which had been carried out well by the Bulungan Regency KPUD during the covid-19 pandemic. The conclusion of the research is that the KPUD in disseminating the general election to young voters has been quite effective, both procedurally, technically and innovatively. Keywords: Covid-19 Pandemic, Effectiveness of Socialization, Regional General Election Commission, Regional Head Elections, Voters Beginner